Factors Associated with the Quality of Life of People Living in Saltwater Intrusion Areas - Chaiyarit, Jitjira; Tuvayanond, Wiput; Intarasaksit, Prat (Unnes Journal of Public Health, 2025)
Saltwater intrusion adversely affects both agriculture and mental health, yet its impact on quality of life (QoL) is underexplored. To understand the profound implications of saltwater intrusion on mental health and quality of life (QoL), especially when combined with other stress factors. The study aims to explore this underexplored relationship in saltwater intrusion-affected zones of Thailand. We investigated the QoL of 417 Thai agriculturists in saltwater-affected areas using the WHOQOL-BREF survey and multiple linear regression. Results indicated that a majority, 61.63%, experienced a moderate QoL, and a significant 83.69% reported tasting salinity in their water. A key finding was that individuals aware of their water’s salinity had notably lower QoL scores. Influential factors on QoL included gender, age, household size, education, and occupation. Specifically, the detection of salinity in drinking water was linked to a 3.16-point reduction in QoL scores (Adjusted Mean Difference: -3.16, 95% CI: -5.08 to -1.25). Furthermore, those with an awareness of water salinity saw an additional QoL decrease of 4.40 points (Adjusted Mean Difference: -4.40, 95% CI: -6.84 to -1.96). The findings underscore the urgency for targeted government interventions to address the repercussions of saltwater intrusion. Strategies including the implementation of real-time alert systems and the establishment of protected freshwater reserves are vital for preserving agricultural productivity, ensuring water security, and enhancing the well-being of affected communities.